Analisis Persepsi Mahasiswa terhadap Metode SQ3R dalam Meningkatkan Pemahaman Bacaan Akademik - Nia Ramadhani; Pota Kusuma Andriyani; Amanda Lorenza; Nayla Roesma Az-Zahra; Iftitah Rizqi Wardhani; Trinil Dwi Turistiani (Universitas Palangka Raya, 2026)
This study was conducted to analyze the effectiveness of the SQ3R method (Survey, Question, Read, Recite, Review) in improving university students’ academic reading comprehension and to identify the factors influencing its implementation in learning activities. The research applied a quantitative approach with a descriptive analytical design. Data were collected through a closed-ended questionnaire based on a Likert scale distributed to 22 students. The research instrument consisted of 20 statements covering reading comprehension, concentration, memory retention, learning effectiveness, and the ease of using the SQ3R method. The collected data were analyzed using descriptive statistics, including frequencies, percentages, and mean scores. The results indicated that most respondents gave positive responses toward the implementation of the SQ3R method. The method was considered effective in helping students better understand academic texts, identify main ideas, improve reading focus, strengthen memory retention, and support learning effectiveness. The stages of SQ3R encouraged students to read more actively, systematically, and purposefully compared to conventional reading methods. Furthermore, students showed a high level of interest in continuing to apply the method in their academic activities. Nevertheless, the effectiveness of the SQ3R method was also influenced by several factors, such as reading interest, study habits, learning environment, and students’ individual abilities. Therefore, the SQ3R method can be used as an alternative reading strategy to improve students’ academic literacy skills.